1979
DOI: 10.1063/1.90850
|View full text |Cite
|
Sign up to set email alerts
|

The Schottky-barrier height of Au on n-Ga1−xAlxAs as a function of AlAs content

Abstract: The Schottky-barrier height of Au on chemically etched n-Ga1−xAlxAs was measured as a function of x. As x increases, the barrier height rises to a value of about 1.2 eV at x≈0.45, then decreases to about 1.0 eV as x approaches 0.83. The barrier height deviates in a linear way from the value predicted by the ’’common-anion’’ rule as the AlAs mole fraction increases. This behavior is related to chemical reactivity of the Ga1−xAlxAs surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1980
1980
2010
2010

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…Figure 1 shows the structure of a typical BEEM sample. We used highly doped (nϭ1ϫ10 18 cm Ϫ3 ) epi-ready GaAs ͑100͒ wafers as substrates to ensure that samples would be conductive enough in subsequent BEEM experiments. Following oxide desorption under As over pressure, a buffer layer with a tapered doping profile was grown.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 shows the structure of a typical BEEM sample. We used highly doped (nϭ1ϫ10 18 cm Ϫ3 ) epi-ready GaAs ͑100͒ wafers as substrates to ensure that samples would be conductive enough in subsequent BEEM experiments. Following oxide desorption under As over pressure, a buffer layer with a tapered doping profile was grown.…”
Section: Methodsmentioning
confidence: 99%
“…Differences as much as 150 meV have been cited. 4 There is also a lack of consensus about the Au/Al x Ga 1Ϫx As Schottky barrier height at different Al concentrations, 17,18 which can be partly attributed to the various sample preparation procedures available.…”
Section: Introductionmentioning
confidence: 99%
“…18 However, ideality factors of metal-Al x Ga 1Ϫx As contacts, exposed to air during device fabrication, were in the range of 1.15-1.3. 26,27 Furthermore, ideality factors were increased up to 1.68 after annealing at 300°C. 27 The devices used in this work were annealed at 300°C for 10 h for the enhancement of thermal stability.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 It was observed that the Ga-O bond is stronger than that of As-O and that Ga atoms preferentially migrate towards the surface leaving vacancies behind in the subsurface region. This behavior can convert the subsurface layer into an Asenriched one.…”
Section: Discussionmentioning
confidence: 99%
“…It does not apply in other situations, e.g. to Al-containing compounds (84), where impurities are likely to occur at the interface. The proposal has been useful in suggesting means to increase barrier heights (85).…”
Section: Electrical Propertiesmentioning
confidence: 99%